The development of geometry learning using traditional dance context assisted by GeoGebra - Wilmintjie Mataheru; Theresia Laurens; Sisilia Marcelina Taihuttu (Jurnal Elemen, 2023)
Research related to crazy bamboo dance, a traditional dance from Maluku and North Maluku, is still oriented towards cultural studies and has not been integrated into mathematics learning. On the other hand, the use of GeoGebra classrooms in previous research mainly refers to the influence on mathematics learning, so there is still a lack of development research based on GeoGebra classrooms that are integrated with cultures such as crazy bamboo dances. The purpose of this study is to produce learning tools in the form of a learning implementation plan (LIP), teaching materials (TM), and student worksheets (SW). In this case, the context of crazy bamboo dance is more focused on the dance medium, namely bamboo, to study tube material. The development model used is a 4D modified model from Thiagarajan. The results of this study produced an RME-based learning tool in the context of crazy bamboo dance assisted by GeoGebra classrooms that are valid, practical, and effective. In addition, the products produced can be used in geometry learning by teachers and students. Still, through this research, teachers can design and develop ethnomathematics-based learning tools by integrating them with the available mathematics software, one of which is Geogebra Classroom.